Marketing Academic Libraries. - Mallon, Melissa (Public Services Quarterly)
The article reviews several websites including website of Klout Inc., located at www.klout.com, website of Easel.ly that provides an intuitive, clean interface located at www.easel.ly and the website of the company QRHacker.Com, a Quick Response (QR) code generator, located at www.qrhacker.com.